A Rare Case of Ileal Intussusception Caused by Primary Small Bowel Trichobezoar and Meckel's Diverticulum in an Autistic Child - Marwa Messaoud (22827959) (2025)
Intussusception is a condition in which one part of the intestine slides into an adjacent part of the intestine. Intussusception is an important cause of an acute abdomen and the second most common cause of bowel obstruction in children. Trichobezoars, which are rare in children and often linked to psychiatric disorders, seldom cause intestinal intussusception. While Rapunzel syndrome—a form of gastric trichobezoar extending into the small bowel—is a recognized cause, primary small‐bowel trichobezoars are exceptionally rare. We report a unique pediatric case of ileo‐ileal intussusception triggered by a 30‐cm primary small‐bowel trichobezoar coexisting with Meckel's diverticulum, an association not previously documented. A 6‐year‐old autistic boy presented with symptoms suggestive of bowel obstruction. Imaging suggested small‐bowel intussusception related to Meckel's diverticulum. Surgery revealed an ileo‐ileal intussusception secondary to a 30‐cm obstructive trichobezoar located proximal to the invagination and an inflamed Meckel's diverticulum. The diverticulum was resected, the trichobezoar was removed, and ileo‐ileal anastomosis was performed, with no postoperative complications. The combination of a primary small‐bowel trichobezoar and Meckel's diverticulum leading to intussusception is exceedingly rare and poses unique diagnostic and therapeutic challenges, particularly in special pediatric populations. Early recognition and surgical intervention are essential to prevent bowel ischemia, perforation, and sepsis. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ccr3.70745